Differentiation Strategies and Dynamic Marketing Capabilities in Improving Indonesia's Rice Competitiveness: Sustainable Marketing Approaches and Business Ethics - Hendra Hendra; E. Hasanuddin; Suryono Efendi (Devotion : Journal of Research and Community Service, 2026)
Indonesia's rice industry faces significant challenges in enhancing its competitiveness in the global market. This study aims to develop an integrative model that explains the influence of differentiation strategies and dynamic marketing capabilities on Indonesia's rice competitiveness, considering the role of sustainable marketing moderation and global business ethics. The method employed is qualitative descriptive, pursued through a qualitative design that involves an in-depth assessment of primary and secondary data from the rice industry. The study finds that differentiation strategies and dynamic marketing capabilities exert a positive and significant impact on the competitiveness of Indonesian rice, with sustainability principles and global business ethics reinforcing these effects. This research goes beyond traditional price- and productivity-based approaches by developing an integrative model that positions sustainable marketing and global business ethics as moderating variables. The findings highlight the strategic role of adaptive marketing and value innovation in strengthening national rice competitiveness amid inflation and policy uncertainty, underscoring the need for evidence-based policy briefs addressing the rice trade industry and shifting consumer preferences. These findings contribute theoretically to the development of dynamic marketing capability in the agribusiness sector, as well as practically, informing sustainable food policy formulation in Indonesia.